Profiling of plant extracts (crotion gratissimus and leonotis leonurus) for their activity against mycobacterium tuberculosis and isolation and charecterisation of the active compounds - Maifo, Bochilo Pleasure (My University, 2021)
Tuberculosis is one of the top 10 leading causes of death in the world. The development of drug resistant strains of Mycobacterium tuberculosis such as Multidrug resistant (MDR) and Extensively drug resistant (XDR) strains further complicate the TB control. Medicinal plants present a possible source for new potential antitubercular drugs. They have played an important role in drug discovery, with many pharmaceutical products originating from them. Isolation and characterisation of new antitubercular compounds from plant extracts is relevant today because of the development of resistant strains. The aim of the study was to evaluate the antimycobacterial activity of the leave extracts of Croton gratissimus and Leonotis leonorus. The first step was to extract fine powder leaves of the two plant species using four (dichloromethane, acetone, hexane and ethanol/water) different solvent systems. Isolation of the fractions was done using column chromatography and preparative thin layer chromatography. Minimum inhibitory concentrations were determined using the broth dilution method and the values were recorded in μg/mL. All the isolated fractions from both plant species were evaluated for preliminary in-vitro antimycobacterial activity. Some of the isolated fractions showed an increased activity against the pathogen as compared to the crude extracts. All the crude extracts of the two plants had activity with MIC90 values greater than 125 μg/mL. Seven fractions obtained from Croton gratissimus showed potential activity against the pathogen with MIC90 values ranging from 30.61 to 64.88 μg/mL. Leonotis leonurus had three fractions with promising activity with MICs ranging from 1.963 to 62.51 μg/mL. The crude extracts of the two plant species showed that the two plant species have antioxidant properties. The qualitative antioxidant assay showed that DCM crude extracts had more antioxidants than all other extracts because of more clear zones against the purple background colour on the TLC plates. These was confirmed by the qualitative antioxidant assay where DCM crude extracts was able to inhibit the highest percentage of DPPH at different concentrations than all other solvent extracts. The DCM crude extracts of L. leonurus and Croton gratissimus inhibited 87 and 93 % of DPPH respectively at 250 μg/mL. The structures of the compounds within the isolated fractions were elucidated using NMR and confirmed by MS and FTIR spectroscopies. The NMR data showed that the isolated fractions were not pure compounds but mixtures of closely related compounds. The compounds whose structures were elucidated included two labdane diterpenoids (Croton A and Croton B) and a Cembranolide ((5E,10E,13R)-4-isopropyl-7,11-dimethyl-15-oxo-14-oxa-bicyclo [11.2.1] hexadeca-5,10-dien-7-yl acetate) from Croton gratissimus and a phenol (4-(3,3,4,4-tetramethylheptyl) benzene-1,2-diol)) from Leonotis leonurus.
Thesis (M. Sc. (Chemistry)) -- University of Limpopo, 2021
Keywords: Tuberculosis; Drug resistant strains; External drug resistant; Mycobacterial diseases; Natural immunity; Medicinal plants; Multidrug-resistant tuberculosis